Analysis of the Mediation Effect of Green Competitive Advantage: Reviewing the Influence of Green Innovation on SMEs' Business Performance - Sudirman, Acai; Kusuma, Rr. Chusnu Syarifa Diah; Halim, Fitria; Sembiring, Lenny Dermawan (International Journal of Business, Law, and Education, 2024)
To achieve sustainability and meet the demands of an increasingly environmentally conscious market, many SMEs have begun to adopt environmentally friendly innovations as part of their business strategies. This innovation is expected to improve environmental performance and strengthen the company's competitiveness. This study aims to analyze the mediating role of green competitive advantage in the relationship between green innovation and business performance in small and medium enterprises. The number of samples used was 110 respondents, as determined by the purposive sampling method. The collected data were analyzed using the path and SEM-PLS methods. The results of this study confirm that green innovation has a positive and significant effect on green competitive advantage. Furthermore, green innovation and green competitive advantage have a positive and significant effect on business performance. The mediation effect analysis also proves that green competitive advantage can mediate the relationship between green innovation and business performance. These findings provide important implications for entrepreneurs and policymakers, who can consider environmentally friendly competitive advantage as an essential factor in designing sustainability strategies to improve SMEs' competitiveness and business performance